Pelanggaran Etika Dan Profesi Hukum Dalam Kasus Suap Eks Ketua Pengadilan Negeri Jakarta Selatan (Studi Putusan Pengadilan Negeri Jakarta Pusat Nomor 70/Pid.Sus-TPK/2025/PN.Jkt.Pst) - Ratihpuspita Krisnowo; Syaharie Jaang (Law Department, University of Widya Gama Mahakam Samarinda, 2026)
The effectiveness of law enforcement is shaped not only by statutory provisions but also by the moral integrity and ethical accountability of those entrusted with judicial authority. The bribery case involving the former Head of the South Jakarta District Court, adjudicated under Decision Number 70/Pid.Sus-TPK/2025/PN.Jkt.Pst and subsequently affirmed with an increased sentence in Appeal Decision Number 4/PID.SUS-TPK/2026/PT DKI, illustrates a grave breach of both anti-corruption law and judicial ethical standards. This study draws upon Soerjono Soekanto’s law enforcement theory, deterrence theory, and the concept of institutional integrity to examine the case. Employing normative legal research with statutory and conceptual approaches, the analysis is based on primary legal sources, including anti-corruption statutes, the Judicial Power Act, the Code of Judicial Ethics, and relevant court rulings, complemented by doctrinal and scholarly references. The findings indicate that criminal prosecution serves not only as a punitive response but also as a structural corrective mechanism against corruption within the judiciary. The appellate court’s decision to enhance the sentence, accompanied by fines and restitution, reflects proportionality in sentencing and reinforces both general and specific deterrence. Moreover, ethical misconduct by judges erodes institutional credibility and weakens public confidence in the justice system. The study concludes that the integration of criminal liability and ethical enforcement is essential to restoring judicial legitimacy and strengthening preventive oversight within the judicial framework.